Study on the static and dynamic performance of active bump-metal mesh foil bearings. (1st February 2023) - Guan, Hanqing; Wei, Kexiang; Mao, Wengui; He, Qingbo; Zou, Hongxiang
Abstract: The gas foil bearing (GFB) is an important component of high-speed, oil-free micro turbomachinery. However, the instability of GFBs under certain conditions hinders their widespread application. The traditional solution is to decrease the continuity of the gas film and increases the structural damping of GFBs through 'passive' structural improvements. Thus, the performances of improved bearings cannot be actively adjusted. This paper proposes an active bump-metal mesh foil bearing (AB-MFB) in which three metal mesh blocks (MMBs) are inserted into the active bump-type foil bearing (ABFB) to control radial preloads through piezoelectric actuators (PZTs) and increase the structural damping. A model coupling of the active-metal mesh substructures, bump foil, and top foil is presented to analyse the mechanical properties of the compliant structure of AB-MFB. Dynamic excitation tests are conducted to validate the model. This study then predicts the static and dynamic performance of the AB-MFB by combining the model and compressible gas Reynolds equation. Finally, the effects of different parameters on the dynamic performance of the AB-MFB are discussed.